2013
DOI: 10.1111/gtc.12044
|View full text |Cite
|
Sign up to set email alerts
|

Non‐centrosomal microtubules regulate F‐actin organization through the suppression of GEFH1 activity

Abstract: Animal cells contain two populations of microtubules: one radiating from the centrosome and the other growing from non‐centrosomal sites. Whether or not they have differing roles in cellular architecture and function remains not fully understood. The cytoplasmic protein Nezha (also known as CAMSAP3) stabilizes non‐centrosomal microtubules by attaching to their minus ends. Here, we found that depletion of CAMSAP3 in HeLa cells resulted in a relative increase in centrosomal microtubules, and this change was acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…These findings are consistent with increased GEF-H1 targeting to the MTs caused by PAK1 phosphorylation. Additional support for our observation came from a recent report by Nagae et al (38), who described the existence of two populations: centrosomal and non-centrosomal MTs. These MT populations were shown to have different biochemical characteristics, mechanisms of stabilization, and preference for GEF-H1 binding.…”
Section: Phosphorylation Of Sersupporting
confidence: 88%
“…These findings are consistent with increased GEF-H1 targeting to the MTs caused by PAK1 phosphorylation. Additional support for our observation came from a recent report by Nagae et al (38), who described the existence of two populations: centrosomal and non-centrosomal MTs. These MT populations were shown to have different biochemical characteristics, mechanisms of stabilization, and preference for GEF-H1 binding.…”
Section: Phosphorylation Of Sersupporting
confidence: 88%
“…CAMSAP3 (also known as Nezha) is a member of the calmodulin-regulatedspectrin-associated proteins (CAMSAP)/Nezha/Patronin family proteins, which bind and stabilize the minus-ends of microtubules (11)(12)(13)(14)(15)(16)(17)(18). In cultured mammalian cells, CAMSAP proteins have been shown to stabilize noncentrosomal microtubules in the cytoplasm or cell junctions (11,14,19,20), suggesting their possible involvement in the spatial regulation of microtubule assembly in polarized cells, such as epithelial-specific longitudinal microtubule alignment.…”
mentioning
confidence: 99%
“…1A) (24,26). Recent work has demonstrated that CAMSAP2 and CAMSAP3 bind MT minus-ends and that depletion of these proteins causes a reduction in MT numbers and changes the MT organization in epithelial cells (28,29). The Caenorhabditis…”
mentioning
confidence: 99%